Analysis of Reproduction and Agri-Food Market of Crop Production in the Conditions of Food Independence of the Region - V. V. Vrublevskaya (Статистика и экономика)
Throughout the existence of mankind, the issues of human nutrition have been of daily relevance. With the development of statehood, their formulations have changed and since the beginning of the 21st century, tasks have been set to provide the population with food of their own production, to develop the reproductive process in agriculture, to achieve food self-sufficiency and independence.The purpose of the study. The purpose of the study is to determine the type of reproduction process in the current situation on the market of crop production in order to assess the level of food self-sufficiency of the population of the Irkutsk region with these products and to develop recommendations for their development.Materials and methods. Statistical methods were used in the paper: descriptive statistics, comparative analysis, dynamic series analysis, monographic and other research methods. The study uses normative, reference and statistical information. The empirical base of the study was made up of data from the Federal State Statistics Service, the Ministry of Agriculture of the Irkutsk region, accounting reports of agricultural organizations, publications in open sources. The object of the study is the supply of crop production in the Irkutsk region on the market.Results. The author’s approach in the study of the reproductive process and the agro-food market of crop production in the Irkutsk region, allowed to comprehensively analyze and determine: the type of reproduction of crop production, namely grain as expanded, potatoes and vegetables as narrowed; the main grain producers are peasant farms, potatoes and vegetables are households of the population; the level of self-sufficiency of the region with crop production, namely the region is self-sufficient with grain and potatoes; the level of food dependence of the region on imports, namely, the region is dependent on the import of vegetables; to identify the factors that influenced the formation of these indexes (natural and climatic, investment, reduction of the rural population, the prevailing eating behavior of the population of the region, etc.).Conclusion. Taking into account the results obtained, economic instability, high dynamics of changes in the external environment, the directions of formation and development of reproduction and agrifood market of crop production in the Irkutsk region are proposed, namely, for the development of grain production, it is necessary to organize and develop production of highly efficient machinery and technologies for processing; the development of potato growing requires significant investments in agricultural organizations and peasant farms for the purchase of equipment for planting, hilling, harvesting, etc., the construction of potato storage facilities, etc.; increasing the level of self-sufficiency with vegetables in the Irkutsk region is possible through the application of the experience of neighboring regions, the joint work of the state and agricultural producers, the allocation of state support and private investment.